A new configuration of winglet longitudinal vortex generator to enhance heat transfer in a rectangular channel. (5th July 2016) - Tang, L.H.; Chu, W.X.; Ahmed, N.; Zeng, M.
Highlights: A new configuration of winglet longitudinal vortex generator in a rectangular channel is introduced. Six types of longitudinal vortex generator configurations are investigated in detail. The numerical results are analyzed from the prospective of field synergy principle. JF factor is used to evaluate the thermal hydraulic performance of all configurations. The common-flow-up delta winglet combined with elliptical pole configuration has the best overall performance. Abstract: In this study, a new configuration of winglet longitudinal vortex generator (LVG) to enhance heat transfer in rectangular channel is introduced. Furthermore, the effects of two new types of LVGs, i.e. the common-flow-up rectangular winglet combined with elliptical pole (Case E) and the common-flow-up delta winglet combined with elliptical pole (Case F), on flow and heat transfer characteristics in a rectangular channel are investigated in detail by three-dimensional CFD numerical simulations. Comparing with the traditional types of winglet LVG (Case A, common-flow-down rectangular winglet; Case B, common-flow-down delta winglet; Case C, common-flow-up rectangular winglet; and Case D, common-flow-up delta winglet), the result reveals that Case F provides the best effectiveness of the heat transfer enhancement. The results were analyzed from the prospective of field synergy principle, it was found that the intersection angles between velocity and temperature gradient of all vortex generator (VG) configurations were smaller than that of smooth channel due to influence of LVGs, which was consistent with the field synergy principle, i.e., the smaller the synergy angle the larger the Nusselt number. Compared by the performance evaluation parameter, the average JF factor in the Reynolds number range for Case A, Case B, Case C, Case D, Case E, and Case F were −5.1%, 3.6%, 0.9%, 6.5%, 1.3%, and 7.4% higher than that of smooth channel, which means Case F had the best overall heat transfer performances.